THE EFFECT OF GUIDED DISCOVERY LEARNING MODEL ON THE STUDENT’S LEARNING ACHIEVEMENT IN VECTOR KINEMATICS TOPIC IN CLASS XI SENIOR HIGH SCHOOL 2 LINTONGNIHUTA ACADEMIC YEAR 2016/2017 - Partogi A.T. Hutapea; Wawan Bunawan; Reza T.D. Sitompul (UNIVERSITAS NEGERI MEDAN, 2019)
This research was aimed to know the student’s achievement using guided discovery learning model and conventional learning about vector kinematics topic. This research employed a quasi-experiment pre-test and post-test with control design. The populations were 59 students grade XI-science in SMAN 2 Lintongnihuta academic year 2016/2017. The samples consist of two classes, one class with 30 students as experiment class and one class as control class with 29 students, while the sampling technique used purposive sampling. The research instrument used an essay test. The data obtained in the study were analysed using Microsoft Excel. The conclusion was there was an effect of Guided Discovery Learning Model on the student’s learning achievement in vector kinematics topic in class XI SMA Negeri 2 Lintongnihuta Academic Year 2016/2017. The observation was done by observer using an observation sheet of student’s activity conclude that activity of students in experiment class more active than control class. Keywords: guided discovery, student’s achievement, vector kinematics